Membran Spermatozoa Hasil Seksing Gradien Albumin Berpengencer Andromed dan Cauda Epididymal Plasma-2 Ditambahkan Kuning Telur (MEMBRANE OF SPERM FOLLOWING GRADIENT ALBUMIN SEXING USING ANDROMED AND CEP-2 SUPPLEMENTED WITH EGG YOLK) - Rita Fitria Purwoistri; Trinil Susilawati; Sri Rahayu (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2013)
The objective of this study was to determine sperm membrane stability after sexing with gradientalbumin (egg white) using andromed and CEP-2 supplemented with 10% egg yolk. The observations ofsperm membrane included membrane integrity, uncapacitated, capacitated and acrosome reacted. Albumingradient was made by mixing egg white with andromed or CEP-2 supplemented with 10% egg yolk resultingin a concentration of egg whites 10%, 30% and 50%. Membrane integrity was observed using HOST(Hypoosmotic Swelling Test), while uncapacitated, capacitated and acrosome reacted sperm were observedusing CTC (Chlortetracycline) staining. The results showed that both andromed and CEP-2 supplementedwith 10% egg yolk could protect membrane integrity, uncapacitated, capacitated and acrosome reactedsperm. Andromed and CEP-2 supplement with 10% egg yolk could reduce the demage of membrane integrityand uncapacitated sperm, whereas capacitated and acrosome reacted sperm could be kept low.